2007
DOI: 10.1111/j.1365-2958.2007.05937.x
|View full text |Cite
|
Sign up to set email alerts
|

Connecting primary and secondary metabolism: AreB, an IclR‐like protein, binds the AREccaR sequence of S. clavuligerus and modulates leucine biosynthesis and cephamycin C and clavulanic acid production

Abstract: SummaryA protein binding to the autoregulatory element (ARE) upstream of the regulatory ccaR gene of Streptomyces clavuligerus was isolated previously by DNA affinity binding. The areB gene, encoding this protein, is located upstream and in opposite orientation to the leuCD operon of S. clavuligerus; it encodes a 239-amino-acid protein of the IclR family with a helix-turn-helix motif at the N-terminal region. An areB-deleted mutant, S. clavuligerus DareB, has been constructed by gene replacement. This strain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…If this set of nucleotides were those directly bound by TtgV, this may explain why the affinity of TtgV for the ttgD operator is higher and correlates with the lower expression of the ttgDEF operon in vivo. Long palindromic DNA targets for IclR family members have been described recently for Streptomyces CcaR, a regulator involved in the control of ␤-lactam antibiotics in this microorganism (25), and Acinetobacter PcaU, a regulator involved in the metabolism of aromatic carboxylic acids (7).…”
Section: Discussionmentioning
confidence: 99%
“…If this set of nucleotides were those directly bound by TtgV, this may explain why the affinity of TtgV for the ttgD operator is higher and correlates with the lower expression of the ttgDEF operon in vivo. Long palindromic DNA targets for IclR family members have been described recently for Streptomyces CcaR, a regulator involved in the control of ␤-lactam antibiotics in this microorganism (25), and Acinetobacter PcaU, a regulator involved in the metabolism of aromatic carboxylic acids (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the chromosome, ndgR is positioned adjacent to leuCD encoding isopropylmalate dehydrogenase subunits. Two independent studies with S. clavuligerus and S. coelicolor demonstrated that NdgR positively regulated leuCD expression (26,31). However, knockout of ndgR and its ortholog had far-reaching impacts on the production of antibiotics such as ACT-undecylprodigiosin (Red) and clavulanic acid-cephamycin.…”
mentioning
confidence: 99%
“…Although it is very important to understand how gene regulators control primary and secondary metabolism, there have been only a few studies on regulators directly linking primary and secondary metabolism in S. coelicolor (30). In addition, there are not many reports on regulators that simultaneously control primary metabolism as well as antibiotic production by directly binding to corresponding promoter regions such as actII-ORF4, cdaR, and redZ (22).…”
Section: Discussionmentioning
confidence: 99%